O papel dos quintais agroflorestais na conservação da agrodiversidade - Tello López, Alex Mauri (Universidade Federal de São Carlos, 2016)
Since a long time homegardens have been fulfilling a series of functions and services, representing geographic spaces for the in situ conservation of germplasm, becoming these important areas for the conservation of local agrobiodiversity, besides contributing to food security in many regions The planet. In order to do so, agroforestry yards must also promote the conservation of agrobiodiversity, as well as the provision of environmental services. For such the present work makes an analysis through a bibliographical review to verify if the agroforestry yards are adding to the agrobiodiversity conservation and if the possibility exists to adopt these systems in the current legislations of the São Paulo state as a method of restoration of legal reserves (LR) and permanent preservation areas (PPA). In this respect, it was analyzed the Forestry Law nº 12.651/2012 and the state resolutions SMA nº 44/2008 and SMA nº 32/2014, considering a set of guiding concepts, attributes and standards applied to the ecological services´ analysis prone to being obtained in agroforestry yards. On evaluation of the legal measures relating to the theory of the ecological services, it was featured the concepts related to the cultural issues, regulation and support. It´s been observed that the attributes relating to cultural issues were not explicit in any of the legislations. The analysis of the other concepts highlighted the potentiality and the relevance of embracing agroforestry yards on ecological services´ rendering, inside legal reserve and preservation areas - mainly if the legal requirements embeds the cultural issues.
The role of homegardens in the conservation of agrodiversity
Keywords: Serviços ambientais; Marcos legais; Áreas degradadas; Biodiversidade; Aspectos socioeconômicos; Environmental services; Legal frames; Degraded areas; Biodiversity; Socioeconomic aspects; CIENCIAS AGRARIAS